PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN FARMASI YANG TERDAFTAR PADA BURSA EFEK - Roni Putra Adi (Bilancia : Jurnal Ilmiah Akuntansi, 2017)
The Capital structure is an important issue for any company due to the good and bad Capital structure will have a direct effect on the financial position of the company. Error in determining the Capital structure will have a broad impact. Especially with the huge debt, would place a heavy burden to the company because the company had to bear the burden of still greater. The purpose of this study was to analyze the Influence Assets Structures, Company-CSizte and Profitability Of Capital Structure On PharmaceuticaI Companies Listpd In Indonesia Stock Exchange. This research is expected to contribute to the development of the Science of financial management, and as an input for thefleadership of the company in making decisions related to asset structure, company size and profitability. The analysis technique used in this research is multiple regression analysis were used to test the hypothesized model that statistically, as well as the extent to which the proposed model is consistent with the data sample. The results showed that (1) Structure of assets shown to affect the Capital structure on a pharmaceutical company listed on the Indonesia Stock Exchange period 2009 to 2014 period (2) The size of a company can influence the Capital structure on a pharmaceutical company listed on the Indonesia Stock Exchange period period 2009 to 2014. (3) the profitability shown to affect the Capital structure on a pharmaceutical company listed on the Indonesia Stock Exchange period 2009 to 2014 period (4) together the asset structure, company size and profitability proven to affect Capital structure on a pharmaceutical company listed on the Indonesia Stock Exchange period 2009 to 2014 period. Tujuan penelitian ini adalah untuk menganalisis Pengaruh Struktur Aktiva, Ukuran Perusahaan dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Farmasi Yang Terdaftar Pada Bursa Efek Indonesia. Penelitian ini diharapkan dapat memberikan sumbangan pengembangan ilmu manajemen keuangan, dan sebagai bahan masukan bagi pimpinan perusahaan dalam mengambil kebijakan terkait dengan struktur aktiva, ukuran perusahaan dan profitabilitas. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi berganda yang digunakan untuk menguji model yang dihipotesiskan secara statistik, serta sejauh mana model yang diajukan konsisten dengan data sampel. Hasil penelitian menunjukkan bahwa (1) Struktur aktiva terbukti dapat mempengaruhi struktur modal pada perusahaan farmasi yang terdaftar di Bursa Efek Indonesia periode tahun 2009 sampai dengan periode 2014. (2) Ukuran perusahaan dapat mempengaruhi struktur modal pada perusahaan farmasi yang terdaftar di Bursa Efek Indonesia periode tahun 2009 sampai dengan periode 2014. (3) Profitabilitas terbukti dapat mempengaruhi struktur modal pada perusahaan farmasi yang terdaftar di Bursa Efek Indonesia periode tahun 2009 sampai dengan periode 2014. (4) Secara bersama-sama struktur aktiva, ukuran perusahaan dan profitabilitas terbukti dapat mempengaruhi struktur modal pada perusahaan farmasi yang terdaftar di Bursa Efek Indonesia periode tahun 2009 sampai dengan periode 2014.